THE REACTIONS OF THE MINORITY TOWARDS RACISM IN CRASH - Shandy T. Mibianto; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2013)
Crash shows the life of a community in a multicultural city of Los Angeles in a variety of separate scenes. At the end of the story will be seen a common thread that connects each of the characters and events that they experience with other characters. The interaction of the players in the movie Crash is highly dominated by racial conflict as a result of racism. In the society nowadays, most people usually see racism only by how the majority discriminate the minority like what is reflected in Crash without knowing that Crash also portrays as vividly how the minority react towards the discrimination by the majority. For this reason, I am really interested in analyzing how the minority react towards racial discrimination by the majority and how the main characters of the minority react towards racism by the majority in Crash based on John P. Myers definition of reactions which are deviance, defiance, and avoidance